Performance Evaluation of Urban Drainage Systems Using Hydrological Modeling in Makassar City - Panguriseng, Darwis; Syafaat, Muhammad; Chen, Wei (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Urban flooding remains a critical issue in rapidly growing coastal cities, including Makassar City, Indonesia. Inadequate drainage capacity, land use change, and increasing rainfall intensity contribute to frequent inundation events. This study evaluates the performance of the urban drainage system in Makassar City using hydrological and hydraulic modeling approaches. The objective is to assess channel capacity, flow behavior, and system reliability under design rainfall scenarios. The research applies a quantitative approach using secondary rainfall data, drainage geometry, and land use information. Hydrological analysis estimates peak runoff, while hydraulic simulation evaluates flow capacity and water level conditions within the drainage network. The results indicate that several primary and secondary channels operate beyond their design capacity during peak rainfall events. Flow overflow and backwater effects occur in densely populated areas, particularly near the Pannampu Canal. Comparative analysis with previous studies confirms that insufficient channel dimensions and limited storage capacity are the main causes of system failure. The findings highlight the need for drainage normalization, integrated modeling-based planning, and sustainable urban drainage strategies. This study provides empirical evidence to support data-driven drainage management and flood mitigation policies in Makassar City.